The role of pivot translations in Asian film festivals in Catalonia: Johnny Ma's Old Stone as a case study - Casas-Tost, Helena; Bustins, Sandra (Journal of Audiovisual Translation, 2021)
Pivot translations are very often used in film festivals, but have been granted little consideration from an academic viewpoint. This article analyses the role of pivot languages in audiovisual translation within the framework of Asian film festivals held in Catalonia. There are three aims of this paper: (i) to examine to what extent pivot translations are part of the translation process in films screened in such festivals, (ii) to determine the justifications for their use, and (iii) to analyse the effects of their use from a qualitative perspective. In order to do so, the answers from a questionnaire distributed among the most relevant agents in Asian film festivals in Catalonia will be analysed. Additionally, the Chinese film Old Stone by Johnny Ma that has been translated into and subtitled in Catalan through English as its pivot language, will be presented as a case study. Lay abstract The use of a third language or pivot translation is widespread in film festivals, although very few studies focus on this practice, which usually remains unnoticed by the average spectator. This article seeks to examine just how common this phenomenon is in film festivals and to analyse its impact with a case study, taking the Chinese film Old Stone by Johnny Ma and its translation into Catalan as an example. More precisely, the article aims to answer two questions regarding the use of pivot languages in audiovisual translation. Firstly, to what extent and for what exact purpose are pivot translations currently being used in Asian film festivals in Catalonia? Secondly, how does using a pivot language, in our case English, affect quality?